Adaptation and Evaluation of the Bulgarian Version of Health Education Impact Questionnaire (heiQ-BG) for the Evaluation of Self-Management Education Interventions - Todorova, Elka; Kineva, Todorka; Bozev, Vasil (UNWE Yearbook, 2018)
This paper describes the translation and cultural adaptation of a Bulgarian version of heiQ - a widely used as generic instrument for assessing education interventions in people with chronic diseases. The translation was carried out according to international standards. Comprehensibility, content validity and factorial validity were tested. The items of heiQ-BG were well understood; the structure of the eight scales were replicated. Further studies involving its practical application are warranted.
Keywords: Self-management; Assessment; Chronic disease; Translation; Validation